(untitled) (Journal of Oriental Studies, 2018)
This article examines the Turkic-Arab cultural contacts in the Mamluk period (XIII-XV centuries) on the basis of medieval Arabic and Türkic-Kypchak written monuments. And also, the reflection of the culture of Desht-i-Kipchak in the Arab East is described.